MASS BALANCE AND THERMAL REGIME OF A CRATER GLACIER AT USHKOVSKII VOLCANO - Muravyev Y.D.; Salamatin A.N. (My University, 1990)
A thermal model has been constructed for a steady-state glacier of Ushkovskii Volcano. Analysis of ice mass balance components has revealed elevated heat flow (mean valce 10 W/m2) in the summit crater wich has remained nearly constant over the last 40 years. The measured accumulation rate and temperature distribution in the snow and firn body in the middle of the Gorshkov crater suggest the existence of a considerable uplift (a small embedded crater) overlain by the glaciers. The formulas proposed in this paper can be used to evaluate critical state parameters for unsteady ice masses on the slopes of Klyuchevskoi Volcano.
Keywords: 28.17.23 Моделирование физических процессов; 37.29.35 Современное оледенение; Ушковский